Optimizing xanthophyll concentrations in diets to obtain well-pigmented yolks - Sandeski, Ligia Mara [UNESP]; Ponsano, Elisa Helena Giglio [UNESP]; Neto, Manoel Garcia [UNESP] (Oxford Univ Press, 2014)
The color of the egg yolk depends on the absorption and deposition of the carotenoids in the hen diet and represents a visual characteristic of great effect on the product acceptance. Corn is commonly used as an energy value ingredient for the hen diet formulations, but its pigmenting potential should also be considered for egg yolk color. The objective of this research was to optimize the proportions between yellow and red carotenoids in corn-based rations to provide the maximization of a yolk's color. For our study, Dekalb laying hens were individually allotted in cages to receive the 15 experimental diets defined by means of a central composite design in which the variables were the yellow xanthoplhylls from the diets (yellow corn + corn gluten meal), the yellow supplementary xanthoplhylls (lutein + zeaxanthin), and the red supplementary xanthoplhylls (cantaxanthin) at 3 concentrations each. Production traits were not influenced by treatments. Seven distinct colors were identified with the yolk color fan; the preferred one (9) was provided by the highest yellow pigment concentrations with no red pigments, whereas the most rejected one (14) was provided by the highest concentration of red pigment. The objective color was derived from the interaction between yellow and red xanthophylls, with an important effect of red supplementary xanthophylls on redness. Using response surface analyses, 0.5 mg/hen per day of red pigments and 1.5 mg/hen per day of total yellow pigments were enough to reach maximum redness (color index 14), whereas 2.0 mg/hen per day of total yellow xanthophylls were enough to reach local consumer preference (color index 9).
Keywords: carotenoid; color; corn; xanthophyll